Effects of Zinc Oxide Nanoparticles in HUVEC: Cyto- and Genotoxicity and Functional Impairment After Long-Term and Repetitive Exposure in vitro - Poier N (Dove Medical Press, 2020)
Nikolaus Poier,1,2 Johannes Hochstöger,1,2 Stephan Hackenberg,3 Agmal Scherzad,3 Maximilian Bregenzer,3 Dominik Schopper,1,2 Norbert Kleinsasser1,3 1Department of Otorhinolaryngology, Head and Neck Surgery, Kepler University Hospital, Linz 4021, Austria; 2Medical Faculty, Johannes Kepler University Linz, Linz 4040, Austria; 3Department of Otorhinolaryngology, Plastic, Aesthetic and Reconstructive Head and Neck Surgery, University of Wuerzburg, Würzburg 97080, GermanyCorrespondence: Nikolaus Poier Krankenhausstraße 9, Linz 4021, AustriaTel +43 650 2409889Email nikolaus.poier@kepleruniklinikum.atPurpose: The present study focuses on threshold levels for cytotoxicity after long-term and repetitive exposure for HUVEC as a model for the specific microvascular endothelial system. Furthermore, possible genotoxic effects and functional impairment caused by ZnO NPs in HUVEC are elucidated.Methods: Thresholds for cytotoxic effects are determined by the 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide (MTT) and Annexin V assay. To demonstrate DNA damage, single-cell microgel electrophoresis (comet) assay is performed after exposure to sub-cytotoxic concentrations of ZnO NPs. The proliferation assay, dot blot assay and capillary tube formation assay are also carried out to analyze functional impairment.Results: NPs showed to be spherical in shape with an average size of 45– 55 nm. Long-term exposure as well as repetitive exposure with ZnO NPs exceeding 25 μg/mL lead to decreased viability in HUVEC. In addition, DNA damage was indicated by the comet assay after long-term and repetitive exposure. Twenty-four hours after long-term exposure, the proliferation assay does not show any difference between negative control and exposed cells. Forty-eight hours after exposure, HUVEC show an inverse concentration-related ability to proliferate. The dot blot assay provides evidence that ZnO NPs lead to a decreased release of VEGF, while capillary tube formation assay shows restriction in the ability of HUVEC to build tubes and meshes as a first step in angiogenesis.Conclusion: Sub-cytotoxic concentrations of ZnO NPs lead to DNA damage and functional impairment in HUVEC. Based on these data, ZnO NPs may affect neo-angiogenesis. Further investigation based on tissue cultures is required to elucidate the impact of ZnO NPs on human cell systems.Keywords: zinc oxide, nanoparticles, cytotoxicity, genotoxicity, toxicity